The Half-Life of Happiness: Hedonic Adaptation in the Subjective Well-Being of Poor Slum Dwellers to a Large Improvement in Housing - Galiani, Sebastián (2015)
A fundamental question in economics is whether happiness increases pari passu with improvements in material conditions or whether humans grow accustomed to better conditions over time. We rely on a large-scale experiment to examine what kind of impact the provision of housing to extremely poor populations in Latin America has on subjective measures of well-being over time. The objective is to determine whether poor populations exhibit hedonic adaptation in happiness derived from reducing the shortfall in the satisfaction of their basic needs. Our results are conclusive. We find that subjective perceptions of wellbeing improve substantially for recipients of better housing but that after, on average, eight months, 60% of that gain disappears.